Educator Recruitment Management in Islamic Senior High Schools: A Case Study of MA Al Manshur Popongan Klaten - Tegar Syahid Kalijogo Panotogomo; Farida Aulia; Fatimatuz Zahra; Lina Nurhayati (Penerbit Goodwood, 2026)
Purpose: This study examines educator recruitment management at MA Al Manshur Popongan Klaten, Indonesia, focusing on how the POAC (Planning, Organizing, Actuating, Controlling) functions are implemented throughout the recruitment process to support educational quality.Methodology: A qualitative descriptive case study design was used. Data were collected through semi-structured interviews with the principal and deputy head of curriculum, direct observation of recruitment activities, and document analysis. Data were analyzed using Miles and Huberman’s interactive model with source triangulation.Results: Recruitment follows a structured POAC cycle. Planning is conducted through meetings addressing staffing needs and qualification requirements. Organizing is centralized under the principal. Actuating includes job announcements via offline channels and the NU network, document screening, and a two-stage selection process involving administrative review and interviews. Controlling is carried out through classroom observation, student feedback, and staged placement of new teachers in grades 10 and 11.Conclusions: The recruitment system reflects a functional POAC framework with strong leadership centralization. Improvements are needed in formalizing qualification standards, expanding recruitment channels, and incorporating micro-teaching assessments.Limitations: Findings are limited to a single institution and lack longitudinal performance evaluation of recruited educators. Contributions: This study empirically documents POAC-based recruitment in an Indonesian madrasah and contributes to Islamic educational management literature while offering practical improvements for school recruitment systems.